Double Fudge - Blume, Judy (New York, 2002)
His younger brother's obsession with money and the discovery of long-lost cousins Flora and Fauna provide many embarrassing moments for twelve-year-old Peter.
Keywords: Brothers; Fiction; Family life; Fiction; Money; Fiction; Embarrassment; Fiction; Humorous Stories